Volume 2C: Turbomachinery 2018
DOI: 10.1115/gt2018-76870
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Fully-Coupled CFD Engine Simulations, Applied to a Micro Gas Turbine Engine

Abstract: The development of new generations of aircraft engines with reduced environmental impact heavily relies on high-fidelity 3D numerical analysis of the main engine components, compressor, combustion chamber, turbine and their interactions, including the transient and off-design behavior of the full engine. Unlike component-by-component analysis, which requires separate assumptions for the pressure and temperature boundary conditions for each component, a fully coupled approach requires only knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Tables 1 and 2 present the operational and geometrical parameters of the redesign micro gas turbine employed in this study. The currently investigated turbine geometry differs from the original geometry designed by Schreckling [18], so it is denoted as a redesign variation in the same way other researchers have (for example, see Teixera et al [20]). In the validation stage, three operating points at a 40,000, 80,000, and 120,000 rpm shaft speed are chosen to compare the numerical prediction against the experimental data as well as against the numerical prediction using a different method (throughflow).…”
Section: Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 present the operational and geometrical parameters of the redesign micro gas turbine employed in this study. The currently investigated turbine geometry differs from the original geometry designed by Schreckling [18], so it is denoted as a redesign variation in the same way other researchers have (for example, see Teixera et al [20]). In the validation stage, three operating points at a 40,000, 80,000, and 120,000 rpm shaft speed are chosen to compare the numerical prediction against the experimental data as well as against the numerical prediction using a different method (throughflow).…”
Section: Geometrymentioning
confidence: 99%
“…The unsteady simulation gave more details of transient flow behavior during its operation. Teixera et al [20] demonstrated a capability to perform an integrated fully coupled engine simulation on a redesign of KJ66. The component-to-component interactions were captured using mixing-plane interfaces and a nonlinear harmonic methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Full engine optimizations are inherently computationally expensive and are mostly performed beyond academic research. One such optimization of a KJ66 MGT engine was completed by Teixeira et al (2018) with the aim of reducing fuel burn while maintaining thrust performance.…”
Section: Previous Mixed Flow and Mgt Compressor Researchmentioning
confidence: 99%
“…There have been a few reports on threedimensional whole-engine calculations [8] in recent years. Teixeira and colleagues from Numeca [9,10] conducted steady-state and unsteady-state three-dimensional numerical simulations of the micro turbojet engine KJ66. The total number of grids is approximately 19.2 million, of which the computational domain includes one blade passage for every turbomachinery blade row, a 60 • sector for the combustion chamber, and a half exhaust hood.…”
Section: Introductionmentioning
confidence: 99%